PENGARUH PENGUNGKAPAN CSR, EMISI KARBON DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Kifli, Andi Zulkifli. A.F (Jurnal Akuntansi Trisakti, 2025)
This study aims to test and analyze the effect of CSR disclosure, carbon emission disclosure, capital structure on firm value with company profitability as a variable that moderates the relationship between CSR disclosure, carbon emission disclosure and capital structure on firm value. This type of research is quantitative research. This research was conducted at various industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. Research data in the form of annual reports and sustainability reports obtained from the official website of the Indonesia Stock Exchange and the official website of each company. The sample was 8 companies and 40 data. Sampling using purposive sampling method. The data were analyzed using the Moderated Regression Analysis (MRA) method processed with the Statistical Package for the Social Sciences (SPSS). The results showed that; 1) CSR disclosure has a positive and significant effect on firm value; 2) carbon emission disclosure has a positive and significant effect on firm value; 3) capital structure has a negative and significant effect on firm value; 4) profitability is able to moderate the relationship between CSR disclosure and firm value; 5) profitability is able to moderate the relationship between carbon emission disclosure and firm value; 6) profitability is not able to moderate the relationship between capital structure and firm value.